2012
DOI: 10.7498/aps.61.218501
|View full text |Cite
|
Sign up to set email alerts
|

Two-dimensional numerical analysis of the collection mechanism of single event transient current in NMOSFET

Abstract: The single event effects in NMOSFET at different values of drain bias, gate length and striking location are thoroughly analyzed by two-dimensional numerical simulator in this paper. The results show that single event transient current increases with the increase of drain bias and with the decrease of gate length. Furthermore, single event transient current varies with the electric field at some places in the device. The present study provides important guidance on the devices design of mitigating the single e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 7 publications
0
3
0
Order By: Relevance
“…The time parameter controls the time required for heavy ions to penetrate into the material. It is worth noting that the model uses the LET value as the default parameter, and the conversion relationship between the two units of this parameter is [28]…”
Section: Device Simulation Modelmentioning
confidence: 99%
“…The time parameter controls the time required for heavy ions to penetrate into the material. It is worth noting that the model uses the LET value as the default parameter, and the conversion relationship between the two units of this parameter is [28]…”
Section: Device Simulation Modelmentioning
confidence: 99%
“…[12] Recently, many local studies have been done on the SET characteristics of par-tially depleted (PD)-SOI MOSFETs. [13,14] Most of them analyze the SET characteristics using simulation tools, and few results have been obtained using pulsed laser systems.…”
Section: Introductionmentioning
confidence: 99%
“…Charge collection is usually the sum of drift, diffusion and parasitic bipolar amplification components. [3][4][5] Previous research has shown that the SETs generated in PMOSs dominate the overall SETs, [6][7][8] thus the heavy-ion response mechanisms for PMOSs demand more studies and analysis. To understand the single-event charge collection and distinguish the bipolar effect from the other two components (drift and diffusion), simulations were conducted using devices with and without the source implant (i.e., with and without the emitter junction of the parasitic bipolar transistor).…”
Section: Introductionmentioning
confidence: 99%